2012
DOI: 10.1155/2012/326806
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inhibition of Angiotensin-Converting Enzyme and/or Neutral Endopeptidase on Neuropathy in High-Fat-Fed C57Bl/6J Mice

Abstract: We have demonstrated that treating diet-induced obese (DIO) mice with the vasopeptidase inhibitor ilepatril improved neural function. Vasopeptidase inhibitors block angiotensin-converting enzyme (ACE) and neutral endopeptidase (NEP) activity. We propose that increased activity of ACE and NEP contributes to pathophysiology of DIO. To address this issue C57Bl/6J mice or mice deficient in NEP were fed a high-fat diet and treated with ilepatril, enalapril, ACE inhibitor, or candoxatril, NEP inhibitor, using both p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 41 publications
0
17
1
Order By: Relevance
“…For example, in studies of high-fat fed neprilysin-deficient mice [3, 24], as well as in high-fat fed wild-type mice or rats treated with a neprilysin inhibitor [25, 26], glucose excursions during an i.p. glucose challenge were no different from those observed in high-fat fed wild-type control mice or rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in studies of high-fat fed neprilysin-deficient mice [3, 24], as well as in high-fat fed wild-type mice or rats treated with a neprilysin inhibitor [25, 26], glucose excursions during an i.p. glucose challenge were no different from those observed in high-fat fed wild-type control mice or rats.…”
Section: Discussionmentioning
confidence: 99%
“…Data from previous studies may contradict ours because (1) i.p. glucose administration does not stimulate GLP-1 secretion [3, 24, 25, 26]; (2) in some cases, C57BL/6J purchased from The Jackson Laboratory were used as controls for neprilysin-deficient mice (rather than being bred from mice heterozygous for the null allele) [3, 24, 25], or rats were used [22, 26]; (3) pharmacological inhibition may not completely ablate neprilysin activity as is the case with genetic deletion, (4) in 1-year-old neprilysin-deficient mice, glucose tolerance may have been confounded by weight gain due to their increased food intake [27]; and (5) variances in the duration or timing of dietary/inhibitor intervention may result in different outcomes. Reconciling these differences in future work will be critical for developing a better understanding of the role of neprilysin in modulating glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…This latter study reported that 1-year-old neprilysin-deficient mice on regular chow developed impaired oral glucose tolerance; however, the data may have been confounded by selective weight gain resulting from increased food intake [30]. By contrast, in other studies of genetic neprilysin deficiency, lack of neprilysin activity did not alter the susceptibility of mice to high-fat-diet-induced glucose intolerance and insulin resistance [11,31,32]. Regarding pharmacological studies in animals, while subcutaneous or intravenous administration of a neprilysin inhibitor for an acute period (up to 2 h) [3,[18][19][20] had a positive impact on glucose homeostasis, its oral administration for a 3 month period (12-14 weeks) failed to improve oral [33] or intraperitoneal [32,34,35] glucose tolerance in high-fat-fed or diabetic rodents, suggesting that either the bioavailability of inhibitor is lower when given orally or compensatory mechanisms are activated over time that result in loss of inhibitor efficacy.…”
Section: Arguments Against a Beneficial Effect Of Neprilysin Inhibitimentioning
confidence: 90%
“…In contrast to the above-mentioned positive effects of reduced neprilysin activity on glucose homeostasis, some studies on deficiency/pharmacological inhibition of neprilysin have raised some uncertainty with respect to the potential glycaemic effects of neprilysin inhibitors [11,[30][31][32][33][34][35]. Importantly, none of these studies showed detrimental effects on glycaemic status, except one [30].…”
Section: Arguments Against a Beneficial Effect Of Neprilysin Inhibitimentioning
confidence: 99%
See 1 more Smart Citation